Tarmės Lietuvoje ir Slovėnijoje: sociolingvistinis tyrimas - Kiaušaitė, Gabija (Slavistica Vilnensis, 2012)
Sociolingvistiniai tyrimai yra būtini, norint stebėti, kaip kinta svarbiausias visuomenės komunikacinius poreikius tenkinantis veiksnys ir tautą vienijantis reiškinys — kalba ir jos atmainos [Karaliūnas 2008, 50–55]. Viena rezultatyviausių tyrimo formų yra reprezentatyvus anketavimas ir gautų atsakymų analizė. Sociolingvistinius pokyčius tam tikroje šalyje (visuomenėje) rodantys tyrimo rezultatai gali būti gretinami su pagal tą pačią metodiką atlikto sociolingvistinio tyrimo rezultatais kitoje šalyje (visuomenėje). Tai leidžia stebėti įvairias panašių (arba vienodų) šiuolaikinių globalinių procesų tendencijas ir rezultatus....Gabija KiaušaitėDialects in Lithuania and Slovenia: a Sociolinguistic StudyThe article is based on a detailed survey designed to discuss the dialect usage and attitudes in Lithuania and Slovenia. The sociolinguistic investigation strongly supported by quantitative data helped to compare the attitudes of Lithuanian and Slovenian respondents in specific speech communities, their social roles and communicative situations.It was found that Lithuanian dialects have a less overt prestige as compared to Slovenian dialect usage in the public and hometown area. Lithuanian attitudes toward their own and other dialects are much less positive. In addition to that, the quantitative data has revealed the differences in the attitude of Lithuanian and Slovenian inhabitants regarding the importance of dialect in connection with the national identity. The questionnaire was administered during March and April of 2012. It consisted of multiple choice questions. The respondents were asked to fill the questionnaire over the Internet.Overall, the survey of Lithuanian and Slovenian inhabitants shows that the process of urbanization may be affecting Lithuania much more than Slovenia, where a viable and significant variation of dialects is still observable.Keywords: sociolinguistic, dialects, Lithuanian, Slovenian.